ПЕРКУТАННАЯ НЕФРОЛИТОТОМИЯ В ЛЕЧЕНИИ КРУПНЫХ И КОРАЛЛОВИДНЫХ КАМНЕЙ ПОЧЕК (Вестник урологии, 2015)
Management of large and staghorn renal calculi is an actual urology problem. Authors analyzed 808 percutaneous nephrolithotomies (PNL), performed for 613 patients since 2010 to 2014. There were used most modern PNL procedures: multiple access, miniPNL, combined approach to kidney. Demonstrated high effectiveness of this method – 74% stone free rate, associated with low complication level for Clavien scale – 3 level – 5,6% of patients, 4 – 1,6%. No deaths and nephrectomies were observed. Procedures, which authors rated as optimizing treatment and decreasing complications, include miniPNL, tubeless PNL. Prone position is recommended as most comfortable. Puncture is performing using ultrasound probe, without adapter (free hand technic). Third part of all operations were done without previous retrograde ureter catheterizing, this trick allows do operation faster, decreases invasiveness and time of fluoroscopy. Optimal technic of access dilating was found using one or two shots Amplats sheath placement. Most dangerous complications are urosepsis and bleeding. 5 cases of arterio-venous fistula or pseudoaneurism were noticed, which are treated endovascular. PNL demonstrate well results and low complication level for treating of large and staghorn renal stones.